The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1002/ijc.2910300110
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical demonstration of an ovarian cancer‐associated urinary peptide

Abstract: Immunization with a peptide fraction from ovarian cancer urine resulted in an antiserum that reacts with a 6,000 dalton (6K) peptide. In urine from some patients with advanced gynaecological cancer, the concentration of 6K peptide was high enough to be detected by immunodiffusion. By radioimmunoassay the levels in normal serum could be determined. The concentrations in serum was 5-20 microgram/l and that in urine 5-50 microgram/l. Elevated levels were observed in urine from 5 out of 8 patients with ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
83
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 12 publications
1
83
0
Order By: Relevance
“…2), which is also known as pancreatic secretory trypsin inhibitor and tumor-associated trypsin inhibitor (3), is mainly produced in the acinar cells of the exocrine pancreas. The role of SPINK1 is postulated to be the prevention of inadvertent proteolysis in the pancreas caused by intra-acinar premature activation of trypsinogen (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…2), which is also known as pancreatic secretory trypsin inhibitor and tumor-associated trypsin inhibitor (3), is mainly produced in the acinar cells of the exocrine pancreas. The role of SPINK1 is postulated to be the prevention of inadvertent proteolysis in the pancreas caused by intra-acinar premature activation of trypsinogen (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…1), which is also known as pancreatic secretory trypsin inhibitor and tumor-associated trypsin inhibitor, is mainly produced in the acinar cells of the exocrine pancreas. Tumor-associated trypsin inhibitor was initially isolated from the urine of a patient with ovarian cancer (2) and was later found to be identical to SPINK1 (3). The role of SPINK1 has been postulated to be the prevention of inadvertent proteolysis in the pancreas caused by intra-acinar premature activation of trypsinogen (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Serine protease inhibitors are secreted not only from normal tissue but also from cancerous tissue and different tumor cell lines [1][2][3]. It has been previously shown that the HPSTI, primarily a pancreatic secretory product, is also secreted from different human tumor cell lines in serum-free medium.…”
Section: Introductionmentioning
confidence: 99%